PENGARUH PROFITABILITAS, STRUKTUR ASET, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN DENGAN STRUKTUR MODAL SEBAGAI VARIABEL INTERVENING - Nur'aini, Fitri; Hamid, Mudasetia (LPPM Universitas Bina Bangsa, 2025)
This study aims to analyze the influence of profitability, asset structure, and company size on company value with capital structure as an intervening variable. The population in this study is insurance sub-sector companies listed on the Indonesia Stock Exchange for the 2019-2023 period. The sample in this study includes 8 companies with a total of 40 research data. The sampling technique uses the purposive sampling method. The research method used is quantitative with data sources in the form of secondary data. The data analysis method uses multiple linear regression analysis and path analysis with SPSS version 30. The results of this study conclude that profitability and asset structure do not have a significant effect on the value of the company, while the size of the company and capital structure have a significant effect on the value of the company. Profitability has a significant effect on capital structure, whereas asset structure and company size do not have a significant effect on capital structure. The results of the path analysis test stated that profitability had no effect on the company's value through the capital structure, while the company's asset structure and size had an effect on the company's value through the capital structure.